Identifying opportunities for shared decision-making through patients’ and physicians’ perceptions on the diagnostic process: A qualitative analysis of malpractice claims in general practice - Sofie Jacobse; Hanneke Rijkels-Otters; Manon Eikens-Jansen; Trudy van der Weijden; Glyn Elwyn; Walter van den Broek; Patrick Bindels; Laura Zwaan (European Journal of General Practice)
Background Shared decision-making (SDM) is considered the preferred communication model, yet its applicability in the diagnostic process is understudied.Objective To identify clinical situations in the diagnostic process that could benefit from SDM.Methods An observational study of closed malpractice claims against general practitioners (2012–2020) related to problems of diagnosis, obtained from a liability insurance company in the Netherlands. We established SDM-selection criteria, specified for the diagnostic process (i.e. diagnostic uncertainty, multiple options and clinical equipoise). Phase 1: We selected and categorised eligible cases, using summarised information from a claim database. Phase 2: We analysed 90 fully documented claims and extracted information from GPs and patients related to the diagnostic process. Using this data, we conducted an inductive thematic analysis.Results Phase 1: 261 out of 1477 claims (18%) met the SDM-selection criteria. The main reason for complaints was (omitted) test-ordering (155 claims, 59.4%). The most frequent final diagnoses were: fracture (49%), malignancy (10%), infection (9%), tendon rupture (8%) and cardiovascular disease (4%). Phase 2: Six types of diagnostic considerations emerged from the data: diagnostic uncertainty, using time as a diagnostic tool, management consequences, information about test indication or procedure, indications for re-evaluation and individual patient context. Contradictory statements from GPs and patients demonstrated a lack of shared understanding.Conclusion The diagnostic process could benefit from SDM in several areas, including discussing diagnostic options, test conditions (e.g. timing and procedure) and follow-up. SDM training programs should be tailored to encourage clinicians to apply SDM in diagnostic decisions.